PENGUJIAN ALGORITMA GENETIKA PADA SISTEM PENJADWALAN PENGUJI TUGAS AKHIR UNIVERSITAS AMIKOM YOGYAKARTA - Windha Mega PD; Haryoko Haryoko (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2018)
The scheduling of the final project / thesis lecturer examiners must be in accordance with the competency of the examining lecturer. In addition to considering the competency of examiners, the scheduling process must pay attention to several aspects, including the availability of rooms used in the session, the available schedule of examiners and the number of available sessions.So we need a final assignment examiner information system with Genetic algorithms, and calculate the accuracy value using k-fold cross validation. Through the approach of Genetic Algorithm, it is expected that the system designed to produce the most optimal final / thesis exam schedule based on fitness values, considering this algorithm uses a combination of the principle of natural selection and inheritance in order to get individuals or schedules as expected. The stages of algorithm testing using lecturer datasets, the field of lecturer science, the concentration of lecturers, students, the field of student knowledge and the concentration of students obtained from the Amikom website. The results of the tests were carried out statistical tests to find out the results of applying Genetic Algorithms. Then it will be concluded whether it has answered the problem statement and according to the research objectives. Berdasarkan hasil pengujian didapatkan nilai optimal berada pada kombinasi Probabilitas Crossover 0.7 dan Probabilitas Mutasi 0.4